Preparation and Characterization of High-Density Polyethylene/Polystyrene/Clay Nanocomposites - Azizy, Sussan (2011)
Polymer/clay nanocomposites, materials composed of polymer matrices and clay particles with which at least one dimension of the clay particles is in the nanometer range. The nanocomposites exhibit significant improvement of some properties compared to those of the original polymers. Blend of polyethylene (PE) and polystyrene (PS) are widely used in industry but suffer from some drawbacks such as low toughness and low service temperature. This work is an attempt to overcome the disadvantages of high density polyethylene/polystyrene (HDPE/PS) blends through the addition of clay by melt blending to produce HDPE/PS/clay nanocomposites. In order to improve compatibility between polymer and clay particles, sodium montmorillonite (Na-MMT) was modified by octadecylamine (ODA) to produce octadecylamine montmorillonite (ODA-MMT). Preparation of the nanocomposites was carried out by melt blending of the ODA-MMT and the HDPE/PS blends in the ratio of 80/20 using an internal mixer. The nanocomposites were characterized using transmission electron microscopy (TEM), x-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and tensile testing. The x-ray data and TEM images of the nanocomposites exhibit that the polymer has been intercalated into MMT layers. The tensile strength and tensile modulus of the nanocomposites improve with the increase of organoclay content. Meanwhile, the percentage of elongation at break decreases with the addition of the filler. TGA results show thermal stability of the nanocomposites improves with the increase of organoclay content of up to 5.00 wt% compared to that of the polymer blend. The SEM micrographs reveal that the presence of organoclay slightly promotes the miscibility of the polymer phases and somewhat decreases the flexibility of nanocomposite. In order to improve further HDPE/PS nanocomposite properties, PE-gr-MA was added into the composites. The optimum concentration of PE-gr-MA, based on x-ray data and maximum tensile properties was 1.00 wt%. The x-ray and TEM results of the nanocomposites reveal that the nanocomposites have intercalated structure. The thermal stability and tensile properties of nanocomposites are enhanced compared to that of the original nanocomposites. The SEM micrographs show that the presence of PE-gr-MA greatly increases miscibility but decreases the flexibility of the nanocomposites.